Emotional Manipulation in the Name of Love: A Feminist and Hyperrealist Analysis of “Treat You Better” - Sabtiana, Rela (CV. AFDIFAL MAJU BERKAH, 2025)
This study explores gender dynamics and emotional manipulation in Shawn Mendes’ song Treat You Better through the lens of feminist theory and Baudrillard’s concept of hyperreality. The lyrics center on a male persona who asserts that he can treat a woman better than her current partner. While this narrative appears empathetic and caring, it subtly conveys a form of benevolent coercion, in which the man positions himself as morally superior and thus more deserving of the woman’s affection. This analysis employs qualitative textual methods to examine the linguistic structure and implicit meanings embedded in the song’s lyrics. The findings reveal that expressions of concern are often framed as emotional domination, cloaked in seemingly affectionate language. Baudrillard’s hyperreality theory is used to illustrate how media representations of romantic love contribute to distorted ideals of relationships, obscuring the boundary between genuine care and controlling behavior. The study concludes that popular media, including songs like Treat You Better, may perpetuate patriarchal norms and emotional manipulation under the guise of romantic concern. By critically examining such portrayals, this research underscores the importance of media literacy and gender awareness. It reinforces global efforts toward achieving SDG 5 (Gender Equality) and SDG 4 (Quality Education).